An??lise dos resultados do programa Acessa SUS na judicializa????o de medicamentos na grande S??o Paulo - SP - Cirico, Priscila Freitas (2019)
In Brazil, the Constitution enacted in 1988 establishes that "health is a right of everyone and the duty of the State", and the Unified Health System (SUS) is based on the universal right to health, equal access, decentralization and participation of society. Even with the progress of the Unified Health System, there are still difficulties to guarantee the population's access to medicines and there are a large number of lawsuits for drug applications resulting in an impact on the financing of pharmaceutical assistance in the SUS. This study aims to analyze the results of the Access SUS Program, implemented in Grande S??o Paulo in the year 2017 with the main objective of conducting pharmaceutical and nutritional orientation, seeking the rational provision and reduction of legal actions to obtain medicines. This is a quantitative documentary research based on reports and presentations of results provided by the State Department of Health of S??o Paulo (SES / SP), with data coming from the service Programa Acessa SUS between February 2017 and July 2018 and of lawsuits served by SES-SP between January 2014 and August 2018. Data were analyzed using Microsoft?? Excel Software for Windows 2016 using descriptive statistics. The results show that R $ 796,993,815.29 was spent with lawsuits between 2014 and 2018 and that in 2017 there was a 3% decrease in the number of lawsuits and a 5% decrease in legal expenses compared to 2016. In addition, we can consider that 34% of lawsuits for drug solicitation could have been avoided between the years 2014 and 2018 since they are drugs that are part of the SUS distribution list, which demonstrates the potential of the Programa Acessa SUS.